Cognitive Autocracy of the Object as a Theoretical Presupposition of Foundational Analyses in Epistemology: A Historical Review - Akpan, Etorobong Godwin (Titian: Jurnal Ilmu Humaniora, 2022)
A historical review of epistemology was carried out. The objective of the study was to demonstrate through historical data that the underlying presupposition that rules epistemological analysis is the cognitive autocracy of the object. To achieve this objective, the method of content analysis with a special focus on the traditional historical method was adopted for the study. With the application of the historical method to the data of study, it was easy to demonstrate the validity of the thesis that epistemology is bedevilled by the cognitive autocracy of the object. It was concluded that the problem associated with the presupposition could be obviated if behavioural constructivism as a new approach to epistemology could be switched for rational reductionism.